EDUKASI KETERAMPILAN HARDSKILL MELALUI HANDICRAFT BERBASIS LOGIC EXPLOXER DI DESA KOLBANO KABUPATEN TTS - Budi Kurniawan; Elisabeth Ernawaty Fernandes; Karima Tunisa Palla; Sahrul Tjandring (Program Studi Pendidikan Guru Sekolah Dasar, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Kupang, 2023)
The purpose of this community service is to be able to improve the Hardskill ability of students by providing Hardskill Skills Education training through Logic Exploxer-Based handicrafts in Kolbano Village, TTS Regency regarding: (1) processing of plastic waste into handicrafts (2) processing of various shapes and colors of beach stones become handicrafts.. Implementation of hardskill skills education training service activities through Logic Exploxer-Based Handicraft in Kolbano Village, TTS Regency is conducted according to the planned program. The implementation method used in this community service activity is divided into 4 (four) stages including (1) initial observation of the activity area (2) problem mapping (3) activity socialization (4) training implementation by involving the community, students, and lecturers of the Primary School Teacher Training Study Program University of Muhammadiyah Kupang. The outcome of this activity is the understanding of the community and students about the processing of plastic and colored stone waste and the ability to develop students' hard skills.